2013
DOI: 10.1186/1477-7525-11-114
|View full text |Cite
|
Sign up to set email alerts
|

Absence of social desirability bias in the evaluation of chronic disease self-management interventions

Abstract: BackgroundBias due to social desirability has long been of concern to evaluators relying on self-report data. It is conceivable that health program evaluation is particularly susceptible to social desirability bias as individuals may be inclined to present themselves or certain health behaviors in a more positive light and/or appease the course leader. Thus, the influence of social desirability bias on self-report outcomes was explored in the present study.MethodsData were collected from 331 participants of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 51 publications
0
25
1
Order By: Relevance
“…Given that social norms are integral to children's experiences, there is the possibility that social desirability bias may have impacted on the results. Two potential motivations should be noted; one that relates to M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 13 children achieving the acceptance of the researcher through desirable responses 31 , and the second that is grounded in a preadolescent subculture that emphasises peer acceptance. Further work is certainly warranted to better understand children's attitudes, beliefs and practices related to discretionary food consumption.…”
Section: Limitationsmentioning
confidence: 99%
“…Given that social norms are integral to children's experiences, there is the possibility that social desirability bias may have impacted on the results. Two potential motivations should be noted; one that relates to M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 13 children achieving the acceptance of the researcher through desirable responses 31 , and the second that is grounded in a preadolescent subculture that emphasises peer acceptance. Further work is certainly warranted to better understand children's attitudes, beliefs and practices related to discretionary food consumption.…”
Section: Limitationsmentioning
confidence: 99%
“…Health-education processes to improve literacy in users' health and / or relationships of trust between patient and health professionals, could be associated to combat low adherence to drug therapies. The importance of the control group's result in this study must be highlighted, which could identify a possible phenomenon known as 'social desirability bias', which refers to the fact that interviewees report behavior that they believe represents an acceptable social position (Nolte et al, 2013). This phenomenon may have influenced the interviewees to report greater adherence for both groups (the intervention and control groups).…”
Section: Resultsmentioning
confidence: 97%
“…Seven studies examined the effect of SD in self‐reports of treatment variables and outcomes, and in most of them SD correlated negatively with certain undesirable self‐reports such as psychiatric symptoms or drug addiction severity and correlated positively with desirable characteristics such as parental happiness or treatment attendance. On the contrary, two studies found a negligible effect of SD on clinical outcomes such as therapeutic alliance (Reese et al., ) and self‐management of chronic disease (Nolte, Elsworth, & Osborne, ).…”
Section: Resultsmentioning
confidence: 99%